Assessing local government policies in poverty alleviation: a case study of Pohuwato Regency, Gorontalo - Rusni Djafar; Umar Songga Sune (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the effectiveness of poverty alleviation policies implemented by the Pohuwato Regency Government between 2019 and 2024. Using quantitative data from official reports and qualitative insights from interviews with policymakers and community members, the study identifies trends in poverty, economic growth, and social outcomes. Findings show a modest reduction in poverty from 18.16% in 2019 to 17.11% in 2024, alongside improvements in poverty depth and severity indices. Economic growth contributed to poverty reduction, but income inequality remains high, as indicated by a Gini ratio of 0.413. Community perspectives highlight that while government programs in infrastructure, microfinance, and skills development have helped, challenges persist in rural areas, especially in agriculture. The study emphasizes the importance of inclusive, community-based approaches, stronger regional economic empowerment, and improved monitoring systems to enhance policy effectiveness. The results provide insights for refining local poverty reduction strategies and promoting sustainable livelihoods in Pohuwato Regency.